Dual‐Reactable Fluorescent Probes for Highly Selective and Sensitive Detection of Biological H2S. Issue 9 (1st April 2016) - Wei, Chao; Wang, Runyu; Zhang, Changyu; Xu, Guoce; Li, Yanyan; Zhang, Qiang‐Zhe; Li, Lu‐Yuan; Yi, Long; Xi, Zhen
Abstract: Hydrogen sulfide (H2 S) is an important endogenous signaling molecule with a variety of biological functions. Development of fluorescent probes for highly selective and sensitive detection of H2 S is necessary. We show here that dual‐reactable fluorescent H2 S probes could react with higher selectivity than single‐reactable probes. One of the dual‐reactable probes gives more than 4000‐fold turn‐on response when reacting with H2 S, the largest response among fluorescent H2 S probes reported thus far. In addition, the probe could be used for high‐throughput enzymatic assays and for the detection of Cys‐induced H2 S in cells and in zebrafish. These dual‐reactable probes hold potential for highly selective and sensitive detection of H2 S in biological systems. Abstract : Two heads are better than one : Fluorescent probes with two types of reactive heads (R 1 and R 2 ) for H2 S can lead to a higher selectivity than that of single‐reactable probes (See Figure). The probe was used for highly selective and sensitive detection of biological H2 S.